Survival analysis of cholangiocarcinoma: A 10-year experience in Malaysia - Yusoff, A.R.; Razak, M.M.A.; Yoong, B.K.; Vijeyasingam, R.; Siti, Z.M. (Baishideng Publishing Group Co. Limited, 2012)
AIM: To investigate the clinical features and survival of patients treated for cholangiocarcinoma in our institution and to analyze the factors affecting their survival.